2017
DOI: 10.1108/jhtt-09-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Value perception of world heritage sites and tourism sustainability matters through content analysis of online communications

Abstract: Purpose The debate on tourism sustainability and its contribution to local development has been very active, especially in connection with world heritage sites (WHSs). The analysis conducted was intended to evaluate the role of information and communication technologies (ICTs) in promoting sustainable tourism, stating the relevance given online by local and international operators to the fact a destination was a WHS and to its commitment over sustainability issues. With this aim, the authors aim to take the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The use of ICT to promote sustainable tourism has garnered some attention from scholars too , Garbelli et al, 2017, Isacsson and Gretzel, 2011 On the other hand, we only found a few studies that looked at the use of ICTs for strategic purposes in destination marketing (Buhalis, 2000, Gon et al, 2016, Dickinger and Lalicic, 2016 Malaysian foodservice companies' diffusion of six information technology (IT) applications. Their study highlights multiple diffusion stages for multiple technological innovations in organisations.…”
Section: Strategic Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ICT to promote sustainable tourism has garnered some attention from scholars too , Garbelli et al, 2017, Isacsson and Gretzel, 2011 On the other hand, we only found a few studies that looked at the use of ICTs for strategic purposes in destination marketing (Buhalis, 2000, Gon et al, 2016, Dickinger and Lalicic, 2016 Malaysian foodservice companies' diffusion of six information technology (IT) applications. Their study highlights multiple diffusion stages for multiple technological innovations in organisations.…”
Section: Strategic Ismentioning
confidence: 99%
“…). talked about the ability of ICTs to provide novel ways of approaching marketing, energy monitoring, waste management, and communication for destinations, whileGarbelli et al (2017) suggested how ICTs could be used in order for a destination to offer a proper and complete online…”
mentioning
confidence: 99%
“…Big data analytics could also be used in the hospitality industry for finding guest satisfaction among multiple reviews based on specific words (Xiang et al , 2014), to investigate online reviews on lodging, investigate consumers’ satisfaction or complaints on service experiences, and identify consumer online perceptions (Diaz and Koutra, 2013; Garbelli et al , 2017; Leung et al , 2017a, 2017b; Levy et al , 2013; Raab et al , 2018). By using big data analytics, researchers could easily take out fluff data by finding common schematic and connotative trends in reviews (Xiang et al , 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Outstanding Universal Values (OUV) are presented on and offline. The online presentation of tangible/ICH shall be aimed to foster responsible and respectful behaviour among visitors and raise public awareness about the importance of this heritage (Garbelli, Adukaite & Cantoni, 2017). The digital convergence of Indonesian cultural heritage started by the development of Digital Heritage Network in 1998 as part of the first digital library project initiated by KMRG (Knowledge Management Research Group) of Bandung Institute of Technology in Indonesia (Fahmi, 2002).…”
Section: The Digital Converge Of Indonesian Cultural Heritagementioning
confidence: 99%